OP0050 Fine Mapping and Expression of a Locus Overlapping 3 Types of Inflammatory Arthritis. (23rd January 2014) - Steel, K. J. A.; Hinks, A.; Barton, A.; Eyre, S.; Flynn, E.; Martin, P.; Thomson, W.; ,
Abstract : Background: In a recent fine-mapping study using the Immunochip genotyping array, the RUNX1 region was associated with rheumatoid arthritis (RA p=5×10 -10 ), juvenile idiopathic arthritis (JIA p=1×10 -8 ) and psoriatic arthritis (PsA p=6×10 -4 ). In each disease the SNP rs9979383 confers disease protection with odds ratios ranging from 0.8-0.9. This SNP maps approximately 290kb upstream of the 3' end of RUNX1, indicating that it may potentially be involved in gene regulation. RUNX1 encodes a master transcription factor which has been shown to interact with the regulatory T cell transcription factor FOXP3 as well as regulation of skeletal development. Unlike many loci on the Immunochip array, variation in the RUNX1 region is not well covered, therefore further fine mapping is required. Objectives: To fine map the RUNX1 region and select a SNP suitable for expression studies. Methods: As rs9979383 lies between two points of high recombination, SNPs between these points were selected for fine mapping. 42 common (MAF>0.05) tag SNPs (r 2 >0.9) from the Utah residents (CEPH) with Northern and Western European ancestry (CEU) 1000 genomes July 2010 release were selected using Haploview v.4.2. 2255 RA cases and 1877 healthy controls from the United Kingdom Rheumatoid Arthritis Genetics Group (UKRAGG) were genotyped using the Sequenom iPlex MassARRAY platform. SNPs and samples which reached >90% success rate were included in the analysis. Allelic association testing was performed using PLINK v.1.07 and functional annotation of SNPs was performed using the ASSIMILATOR software programme. Results: In the UKRAG cohort, association with rs9979383 was replicated (p=0.02, OR = 0.9, CI 95% 0.82-0.98) with an odds ratio of 0.9, identical to the previous RA study. No other SNPs in the region showed evidence for association. RUNX1 is highly expressed in CD33+ progenitor cells which are important in generation of immune cells and vascularisation of the synovium. Functional annotation of this SNP indicates that it lies within a region of open chromatin with transcription factor binding potential, making it an ideal candidate for gene expression studies. Conclusions: These results indicate that the RUNX1 association is localised to r99793983 in this RA cohort. This will require further investigation in independent JIA and PsA cohorts but provides evidence that the region is associated with different types of inflammatory arthritis. Currently both whole blood and cell specific expression of the RUNX1 region are underway using individuals with differential genotypes at rs9979383. Combined with the fine mapping this will inform further investigations of the role of RUNX1 in the common pathogenesis of inflammatory arthritis. Disclosure of Interest: None Declared